1999
DOI: 10.1128/jb.181.11.3409-3418.1999
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulation of the esp Genes of Enterohemorrhagic Escherichia coli

Abstract: We have determined that the genes encoding the secreted proteins EspA, EspD, and EspB of enterohemorrhagic Escherichia coli(EHEC) are organized in a single operon. The esp operon is controlled by a promoter located 94 bp upstream from the ATG start codon of the espA gene. The promoter is activated in the early logarithmic growth phase, upon bacterial contact with eukaryotic cells and in response to Ca2+, Mn2+, and HEPES. Transcription of the esp operon seems to be switched off in tightly attached bacteria. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
56
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(63 citation statements)
references
References 47 publications
7
56
0
Order By: Relevance
“…Similar results were observed in at least four other experiments. tivation in serum-free cell culture medium, instead of LB, has been previously shown to 'pre-induce' the ability of EHEC to signal to host cells (Beltrametti et al, 1999). The abilities of wild type and dam-deficient EHEC to stimulate actin assembly were therefore also compared after growth under these conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were observed in at least four other experiments. tivation in serum-free cell culture medium, instead of LB, has been previously shown to 'pre-induce' the ability of EHEC to signal to host cells (Beltrametti et al, 1999). The abilities of wild type and dam-deficient EHEC to stimulate actin assembly were therefore also compared after growth under these conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The environmental cues such as osmolarity, temperature, pH, oxygen, and ions are some of the important signals that bacterial pathogens use to turn-on or turn-off expression of genes critical for colonization and infection in the host. Recent studies have shown that growth of EHEC O157:H7 in media containing high salt concentrations and incubation temperature of 37°C, conditions that closely resemble the intestinal environment, induces the expression of LEE4 operon [37]. It has also been proposed that quorum-sensing signals produced by the normal flora E. coli of the large intestine may represent one of the chemical cues for activating LEE in the early stages of infection [20].…”
Section: Discussionmentioning
confidence: 99%
“…In enterohaemorrhagic E. coli, espADB transcription is initiated at a promoter located in the distal end of the upstream gene sepL, giving a 2.8 kb transcript (Beltrametti et al, 1999). In EPEC, on the other hand, it has been proposed that espADB transcripts begin at the sepL promoter and include the sepL gene (Elliott et al, 1998).…”
Section: Discussionmentioning
confidence: 99%